P026 Sleep during the transition to shift work: Preliminary findings of a longitudinal field study of commencing paramedics. (7th October 2021) - Crowther, M; Ferguson, S; Adams, R; Reynolds, A
Abstract: Paramedics are at increased risk of occupational injuries, mental illness and poor health outcomes. Little is known however about the role of poor sleep in such outcomes and the way in which sleep may change as an individual commences work as a paramedic. The aim of the present study is to investigate changes in sleep as paramedics commence work. As part of an ongoing, longitudinal study of Australian paramedics, participants undertake a baseline assessment prior to commencing work and a follow up every three months for a year. At each time point paramedics wear an actigraph (GENEActiv) for seven days, and complete an online survey including the Pittsburgh Sleep Quality Index (PSQI). The present preliminary analysis utilised linear mixed models to test the effect of commencing work as a paramedic on participants' sleep quality. Preliminary results from the first cohort of recruits are reported (n=9 commencing paramedics, mean age (+SD) = 25.2±4.4, 56% female). There was a significant increase in PSQI scores from baseline (T0: 2.4±1.4) to three months (T1: 5.2±3.9) (F(1, 8) = 5.47, p = 0.05). The percentage of individuals with clinically poor sleep (PSQI ≥5) increased from 0% (n=0) at T0 to 56% (n=5) at T1. Commencing paramedics report significantly poorer sleep quality compared to their pre-commencement levels. Interestingly, baseline PSQI scores indicate no participants were experiencing clinically defined poor sleep. However, at follow-up over half the sample reported clinically defined poor sleep. Findings of objective sleep and wake outcomes are anticipated for the meeting in October.